2004
DOI: 10.4049/jimmunol.173.8.4775
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Productive HIV-1 Infection of Dendritic Cells via Complement Receptor Type 3 (CR3, CD11b/CD18)

Abstract: In the present study, we demonstrate that macrophage-tropic HIV-1 opsonized by complement and limited amounts of anti-HIV-IgG causes up to 10-fold higher productive infection of human monocyte-derived dendritic cells than HIV treated with medium or HIV opsonized by Ab only. Enhanced infection is completely abolished by a mAb specific for the ligand-binding site of CD11b (i.e., α-chain of complement receptor 3, receptor for iC3b), proving the importance of complement receptor 3 in this process. Inhibition of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 29 publications
5
92
0
Order By: Relevance
“…Thus, the fI-mediated processing of C3b fragments on HIV to C3d may have in vivo relevance in the generation of C3d-coated HIV particles with high affinity for CR2 expressed on B cells (or on FDC) promoting an effective transmission of opsonized HIV to T cells. Of note, recent studies have demonstrated complement-mediated enhancement of productive HIV infection in human monocyte-derived dendritic cells (DC) (29). Therefore, processing of C3b fragments to iC3b on HIV might also be involved in the complement-mediated enhancement of HIV infection of monocyte-derived DC through binding of iC3b-coated virus to CR3 and CR4 expressed on DC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the fI-mediated processing of C3b fragments on HIV to C3d may have in vivo relevance in the generation of C3d-coated HIV particles with high affinity for CR2 expressed on B cells (or on FDC) promoting an effective transmission of opsonized HIV to T cells. Of note, recent studies have demonstrated complement-mediated enhancement of productive HIV infection in human monocyte-derived dendritic cells (DC) (29). Therefore, processing of C3b fragments to iC3b on HIV might also be involved in the complement-mediated enhancement of HIV infection of monocyte-derived DC through binding of iC3b-coated virus to CR3 and CR4 expressed on DC.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism is observed in human mononuclear cell lines infected with HIV. CR3 and adhesion particles facilitates HIV-1 penetration into target cells (Stoiber et al 1997, Bajtay et al 2004, Bouhlal et al 2007. Similarly to humans, mTNFα could also be used by viral protein/proteins in cattle to modulate the TNF/TNFR signaling pathway and control BLV replication in CD11b+TNFα+p24+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another macrophage cell surface receptor that has acquired multiple, relatively low-affinity ligand binding activities is the CR3 complement receptor, which recognizes a range of ligands, including opsonized bacteria and viruses, Leishmania surface antigens, intracellular adhesion molecule-1, and fibrinogen, and can also mediate macrophage adhesion (117,118).…”
Section: Why So Many Receptors? Why So Many Ligands?mentioning
confidence: 99%